2009
DOI: 10.1161/circulationaha.108.798561
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Prevents Progression of Heart Failure in Dogs

Abstract: Background-Some studies have shown that metformin activates AMP-activated protein kinase (AMPK) and has a potent cardioprotective effect against ischemia/reperfusion injury. Because AMPK also is activated in animal models of heart failure, we investigated whether metformin decreases cardiomyocyte apoptosis and attenuates the progression of heart failure in dogs. Methods and Results-Treatment with metformin (10 mol/L) protected cultured cardiomyocytes from cell death during exposure to H 2 O 2 (50 mol/L) via AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
214
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(235 citation statements)
references
References 49 publications
16
214
2
2
Order By: Relevance
“…Our observation is consolidated by a recent study which has also shown that Ca 2ϩ -dependent AMPK activation is required for p65/RelA binding to nuclear DNA in thrombin-stimulated endothelial cells, which is mediated by protein kinase C␦ and p38 MAPK (53). In support of our conclusion, other investigators have noted that AMPK can attenuate apoptotic signaling in biological systems other than the endothelium, such as cardiomyocytes (54,55). Capano and Crompton (56) were one of the first investigators to bridge the gaps between AMPK signaling, p38 MAPK, and apoptotic cell death in ischemic hearts.…”
Section: Discussionsupporting
confidence: 89%
“…Our observation is consolidated by a recent study which has also shown that Ca 2ϩ -dependent AMPK activation is required for p65/RelA binding to nuclear DNA in thrombin-stimulated endothelial cells, which is mediated by protein kinase C␦ and p38 MAPK (53). In support of our conclusion, other investigators have noted that AMPK can attenuate apoptotic signaling in biological systems other than the endothelium, such as cardiomyocytes (54,55). Capano and Crompton (56) were one of the first investigators to bridge the gaps between AMPK signaling, p38 MAPK, and apoptotic cell death in ischemic hearts.…”
Section: Discussionsupporting
confidence: 89%
“…Once activated, AMPK promotes catabolic pathways to generate more ATP, and inhibits anabolic pathways, thus allowing for adaptive changes in growth and metabolism under low energy conditions 23. Emerging evidence indicates that AMPK can be activated by metformin in the brain, exerting a neuroprotective role in response to energy depletion through maintaining cellular energy homeostasis,24, 25, 26 promoting mitochondrial biogenesis,27 and increasing brain‐derived neurotrophic factor expression to promote neuronal survival 28. Recently, autophagy has been proposed as a downstream target of AMPK, and AMPK‐induced autophagy activation protects against ischemic injury to peripheral tissue injury29, 30, 31 as well as ischemic brain injury 32.…”
Section: Introductionmentioning
confidence: 99%
“…Three mechanisms have hitherto been proposed. Based on experimental evidence [30][31][32][33][34][35], the main mechanism appears to be the activation of adenosine monophosphate-activated protein kinase (AMPK) [36]. In experimental models of diabetes and HF, metformin activates AMPK, leading to its increased phosphorylation, which, in turn, results in increased phosphorylation of endothelial nitric oxide synthase (eNOS) [30][31][32][33]35].…”
Section: Proposed Mechanismsmentioning
confidence: 99%
“…Based on experimental evidence [30][31][32][33][34][35], the main mechanism appears to be the activation of adenosine monophosphate-activated protein kinase (AMPK) [36]. In experimental models of diabetes and HF, metformin activates AMPK, leading to its increased phosphorylation, which, in turn, results in increased phosphorylation of endothelial nitric oxide synthase (eNOS) [30][31][32][33]35]. Thus, plasma and myocardial levels of nitric oxide increase [30,31], ultimately resulting in improved endothelial function, preservation of left ventricular ejection fraction [30,31,33,35], reduced left ventricular dilatation [30,33,35], improved left ventricular end-diastolic pressure [31,35] and also reduced myocardial autophagy [34] and apoptosis [31].…”
Section: Proposed Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation